"We needed this": perspectives of parents and healthcare professionals involved in a pilot newborn screening program for spinal muscular atrophy. (March 2021) - Kariyawasam, Didu S.T.; D'Silva, Arlene M.; Vetsch, Janine; Wakefield, Claire E.; Wiley, Veronica; Farrar, Michelle A.
Abstract: Background: Newborn screening (NBS) for spinal muscular atrophy (SMA) is a recognised model through which health outcomes can be improved. However, perspectives of parents and healthcare professionals (HCPs) involved in such programs are largely unknown. Methods: A pilot program for SMA ran from August 2018-July 2020. Using a mixed-methods convergent methodology, we used a self-administered questionnaire to understand parents' perceptions and psychological impact of the program from diagnosis to treatment. We thematically analysed successes/challenges encountered by HCPs and recommendations for service improvement from both participant groups. Findings: 202, 388 infants were screened for SMA and the perceptions of 44 parents and HCPs affected by a positive result in eighteen newborns was ascertained. Parents (n=29, 100%) were satisfied with NBS for SMA. Although screen-positive result was distressing for all parents, quality of life improved over time [CarerQoL-7D baseline median score 4 (SD=1.4) vs six-month median score 8 (SD=1.3), p<0.001)]. Challenges for HCPs included managing the time-critical nature of the pathway whilst remaining cognisant of limitations associated with the predictive screening test. Interpretation: Interpretation: NBS for SMA fulfils criteria for population-wide screening. Net benefits are acknowledged by stakeholders to optimise lifelong outcomes. Harms including psychological distress associated with a screen-positive result may be managed by targeted psychosocial support, information provision and a personalised model of care together strengthening healthcare systems. Funding: The NSW Pilot NBS study was funded by Luminesce Alliance. Dr Kariyawasam received funding from the RTP Scholarship, University of New South Wales and The Freedman Family Foundation Scholarship, Sydney Children's Hospital Foundation.